Inventory control practices and recommendation / Dahlan Kidam, Mohd Hamim Imam Mustain and Ridzuan Hussin - Kidam, Dahlan; Imam Mustain, Mohd Hamim; Hussin, Ridzuan (2023)
The control of inventory has, over the years, become one of the main functions of the production manager an area of concern for the finance department and an area of vital importance to the salesman. As a production function, practioners and academicians have applied a variety of analytical techniques to solve the multidimensional problem of inventory control and this paper will highlight some of these mathematical techniques after the project been completed.